Poorly differentiated mast cell tumour and neoangiogenesis: lack of correlation between microvessel density and mast cell density - G. Ranieri; R. Patruno; G. Passantino; A. Chirriatti; A. Perillo; A. Paradiso; L. Passantino (Journal of Biological Research, 2002)
Angiogenesis, a multistep process regulated by positive and negative soluble factors, plays an important role for tumour progression (growth, invasiveness and metastasis).A mutual stimulation occurs between tumour cells and neoplastic cells by paracrine mechanism. Host inflammatory cells can also secrete angiogenic factor. Several experimental researches suggest that Increase of mast-cells density (MCD) Is joined wlt:h Increase of microvessel density (MVD). To evaluate the putative role of MCD in the angiogenic process we studied, for the first time, a series of 16 poorly differentiated grade 3 (G3) dog mastocytomas. Mast cell tumours (MCT) are common in dog with an incidence much higher than those found In human, consequently dog MCT can be a valid model to study angiogenic process. Serial sections for each MCT were processed both wlt:h toluidine bleu specific for MC identification and immunohistochemical method using the polyclonal antibody anti FVIII - RA as an endothelial marker. Slides were evaluated using an image analysis system (Quantimet 500 LeicaJ. The three most vascular areas ••hot spots•• in each tumour tissue were selected and Individual vessels and Individual mast cells were counted at 400.x. Both MVD and MCD means and standard deviation (s.d.) were determined both for each tumour and in the global series. MVD and MCD means value were 18 ± I I and I 06 ± 97 respectively. The regression analysis (pearson-s test) between MVD and MCD failed to show any correlation (p= n.s.). On these basis we speculate that cutaneous malignant mastocytomas are low vascularized tumour and neoplastic mast cells should not playa major role in the angiogenic process.